Magnesium: Nutrition and Homoeostasis - Jürgen Vormann (AIMS Press, 2016)
The essential mineral magnesium is involved in numerous physiological processes. Recommended dietary intake is often not met and a low magnesium status increases the risk for various diseases. Magnesium status is regulated by several magnesium transport systems either in cellular or paracellular pathways. Numerous drugs either interfere with magnesium absorption in the intestines or the reabsorption from primary urine in the kidney. Low magnesium status has been identified as a significant risk factor for several diseases, including type-2 diabetes, cardiovascular diseases, arrhythmias, as well as general muscular and neurological problems. Therefore, an adequate magnesium supply would be of special benefit to our overall health.